Education and Zambia’s Democratic Development: Reconstituting “Something” From the Predatory Project of Neoliberal Globalization - Abdi, Ali A.; Ellis, Lee (Alberta Journal of Educational Research, 2007)
Zambia, a central African country of about 10 million people, is currently exposed to the nonsubjective forces of globalization, including institutional weaknesses such as high unemployment rates and chronic levels of poverty that ipso facto problematize its governance and social development priorities. The first part of the article focuses on an overview of the failure of the formal educational systems in the context of neoliberal globalization. The second part constitutes an examination of ideological orientations underlying neoliberal approaches to the management of the new global economic order. Here the influence of the World Bank in the educational sector is highlighted. The Bank’s ideological orientation is contrasted with educational approaches that should privilege human rights as the standard by which to measure development programs, initiatives, and considerations of ecological integrity. The third section, education for informed action for change through organization, is an overview of the work of a particular activist Zambian civil society association, Women for Change, who work with remote rural communities, especially women. Among the goals of this association is the elimination of poverty through gender analysis, popular education, and advocacy on behalf of marginalized segments of the Zambian population.